2019
DOI: 10.1136/acupmed-2018-011697
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of iatrogenic pneumothorax following acupuncture treatments in Taiwan

Abstract: Background: Pneumothorax is a rare complication of acupuncture and the risk factors are unclear. Objective: This study analysed the incidence of post-acupuncture pneumothorax requiring hospitalisation in a one-million-sample cohort derived from Taiwan’s National Health Insurance Research Database. Methods: We tracked this cohort between 1997 and 2012 and recorded all medical insurance information. Subjects were categorised according to gender, insurance amount, comorbidities, residential area, and number of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Acupuncture and moxibustion therapy on patients have the effect of regulating qi and blood, channeling meridians, and improving yin and yang balance, as well as efficiently preventing and treating diseases [ 17 ]. The gastrointestinal response produced by chemotherapy may be eliminated with acupuncture at Neiguan, Zusanli, and Zhongwan; the KPS score is greatly enhanced, and the therapeutic impact of acupuncture coupled with medications is more visible [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture and moxibustion therapy on patients have the effect of regulating qi and blood, channeling meridians, and improving yin and yang balance, as well as efficiently preventing and treating diseases [ 17 ]. The gastrointestinal response produced by chemotherapy may be eliminated with acupuncture at Neiguan, Zusanli, and Zhongwan; the KPS score is greatly enhanced, and the therapeutic impact of acupuncture coupled with medications is more visible [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports have suggested that multiple bilateral lung punctures can lead to fatal bilateral tension pneumothoraces, even in the absence of a significant pulmonary disease background (15–18). As in this case, lung diseases, such as emphysema, are risk factors for the development of pneumothorax after acupuncture (11,14,16). A previously reported case was of a unilateral pneumothorax (14), and patients with a background of decreased respiratory capacity are more likely to have serious consequences of the occurrence of pneumothoraces.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pneumothoraces following acupuncture is approximately ≤0.001% according to the prospective studies mentioned above (4–10), 0.87 per million sessions in a large study in Taiwan, and 1.75 per million sessions even in high‐risk sites, which is very rare (11). However, the frequency of pneumothoraces among serious adverse events, such as organ damage and death, is relatively high (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Tension pneumothorax is a rare but serious and potentially fatal complication of acupuncture. A history of thoracic surgery, chronic bronchitis, emphysema, pneumonia, tuberculosis, and lung cancer may increase the postacupuncture risk of iatrogenic pneumothorax [ 7 ]. In the present case report, TSS temporarily concealed the underlying tension pneumothorax.…”
Section: Discussionmentioning
confidence: 99%